Children's Thinking / Cognitive Development and Individual Differences - Bjorklund David F. (Thomson/ Wadsworth, 2005)
This book explores the dynamic field of cognitive development, with an increased emphasis on the interactive nature of development. An Introduction to Cognitive Development, Biological Bases of Cognitive Development, The Social Construction of Mind: Sociocultural Perspectives on Cognitive Development, Piget and the Neo-Piagetians, Information-Processing Approaches, Learning to Think on Their Own: The Role of Strategies in Cognitive Development, Infant Perception, Spatial Cognition, Representation, Memory Development, Language Development, Problem Solving and Reasoning, Social Cognition, Schooling and Cognition, Approaches to the Study of Intelligence, Origins and Modification and Stability of Intellectual Differences, Cognitive Development: What Changes and Hoe?, Glossary, References, Credits, Author and Subject Index.